Enhancement of MRI Imaging by Combining Ramp Sampling and Parallel Imaging Techniques in Cerebral Tumors - Hegazy, Ehab A (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Our aim was to decrease geometric distortion artifact in DWI on brain by using different MR techniques such as ramp sampling and parallel imaging. The study was done on 15 patients, They were subject to routine brain MRI examination for different symptoms, examination was done on 1.5 T scanner, patients were divided to three group five patient in each group, geometric distortion in frontal and occipital lobe measured in the routine acquired DWI and after used the interested strategy compared to anatomical T2-FSE acquired in the routine examination then reduction percentage for each strategy was calculated. Application of parallel technique imaging showed significant artifact reduction in frontal lobe with approximately 54.36 % and about 34.8% in occipital lobe, while ramp sampling showed reduction with approximately 19% in frontal lobe and reduced artifact by 41.58% in the occipital lobe. Finally we conclude that using new techniques such as ramp sampling and parallel imaging used with EPI data acquisition reduced geometric distortion artifact and increased geometric resolution.